Rituales viajeros y símbolos de nación en la Institución Libre de Enseñanza: memorias de una excursión a Toledo - Rubén Corchete Martínez (Cahiers de Civilisation Espagnole Contemporaine)
The article analyses a particular case of nation-building focusing on the practice of travelling in the Institución Libre de Enseñanza (Free Institution of Education) and its social circle. In particular, the article points at the Institution’s excursion system, considering it as a ritual practice. To study this issue in more detail, I describe the symbolic structure of some of these rituals through texts of Francisco Giner de los Ríos, Manuel Bartolomé Cossío, and programmes and reports of excursions to Toledo. The source criticism is also supported by empirical evidence from an ethnographic context. In short, I try to show the importance of travelling and its memories in the shaping of what is named «inner Spain», which is a unit of analysis that refers to the ideological and experiential aspects of the nation as imagined political community.